2006
DOI: 10.1094/phyto-96-1148
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity of Ascochyta spp. Infecting Legumes of the Viciae and Cicerae Tribes and Pathogenicity of an Interspecific Hybrid

Abstract: Ascochyta spp. (teleomorphs: Didymella spp.) infect a number of legumes, including many economically important species, and the diseases they cause represent serious limitations of legume production worldwide. Ascochyta rabiei, A. fabae, A. pisi, A. lentis, and A. viciae-villosae are pathogens of chickpea (Cicer arietinum), faba bean (Vicia faba), pea (Pisum sativum), lentil (Lens culinaris), and hairy vetch (V. villosa), respectively. Inoculations in the greenhouse and in growth chambers demonstrated that A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
3
42
0
Order By: Relevance
“…The progeny do not show higher pathogenic fitness than their parents on either host, probably because recombination following hybridization broke up adaptive gene complexes (e.g., see references 18 and 23) controlling fitness on each host. A similar phenomenon was reported by Hernandez-Bello et al (36), who tested hybrids between two closely related Ascochyta species parasitizing faba bean and pea. Among 120 progeny from that cross, only three were pathogenic on pea and none were pathogenic on faba bean, suggesting that host specificity is under polygenic control and crossing these two host-adapted forms broke up gene complexes controlling host specificity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The progeny do not show higher pathogenic fitness than their parents on either host, probably because recombination following hybridization broke up adaptive gene complexes (e.g., see references 18 and 23) controlling fitness on each host. A similar phenomenon was reported by Hernandez-Bello et al (36), who tested hybrids between two closely related Ascochyta species parasitizing faba bean and pea. Among 120 progeny from that cross, only three were pathogenic on pea and none were pathogenic on faba bean, suggesting that host specificity is under polygenic control and crossing these two host-adapted forms broke up gene complexes controlling host specificity.…”
Section: Discussionsupporting
confidence: 80%
“…Previous host specificity studies involved inter-and intraspecific hybridizations of fungal pathogens (15,36). However, despite the potential importance of ecological factors driving genetic divergence, they are poorly understood in fungi (18,22,32,33), and most of the existing data have been obtained from highly artificial experiments (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only A. U. oxytropis, A. U. gansuense, and Fusarium proliferatum have been previously reported to be associated with locoweeds in China (Gao et al, 2012;Zhou et al, 2012;Liu et al, 2016). Other than these three fungal species, only 8 species found in this study have even been reported to be a pathogen of any legume (Tu, 1985;Hernandez-Bello et al, 2006;Asan, 2011;Sharma et al, 2012). Table 6.…”
Section: Discussionmentioning
confidence: 58%
“…), and hairy vetch (V. villosa Roth), respectively. Although these species are host specific (Kaiser et al 1997;Hernandez-Bello et al 2006) under certain conditions, they can infect other species. Little is known of the degree of susceptibility of Vicia spp.…”
mentioning
confidence: 99%